2019
DOI: 10.1093/carcin/bgz174
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial miR-181a-5p promotes glucose metabolism reprogramming in liver cancer by regulating the electron transport chain

Abstract: Liver cancer and other malignant tumor cells rely on the glycolytic pathway to obtain energy (i.e. the Warburg effect); however, the underlying mechanism is unclear. Mitochondria are sites of oxidative phosphorylation and adenosine triphosphate (ATP) production. The 13 constituent respiratory chain proteins encoded by the mitochondrial genome (namely, mtDNA) play essential roles. We found that in human hepatocellular carcinoma (HCC) tissues, 11 out of the 13 mtDNA-encoded genes exhibited decreased mRNA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 45 publications
1
33
0
1
Order By: Relevance
“…[ 25 ] Cohen and Kesler [ 26 ] have found that mitochondrial dysfunctions, encompassing complexes I–IV of the electron transport chain, are characteristics of PD. MT-CYB , encodes the core subunit of complex III, plays a critical role in promoting progression and development of liver cancer, [ 27 ] and is an essential part of the oxidative phosphorylation system, which arouses cellular homeostasis and energy production. [ 28 ] The expression of MT-ND1 is reduced in Parkinson disease with dementia (PDD).…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Cohen and Kesler [ 26 ] have found that mitochondrial dysfunctions, encompassing complexes I–IV of the electron transport chain, are characteristics of PD. MT-CYB , encodes the core subunit of complex III, plays a critical role in promoting progression and development of liver cancer, [ 27 ] and is an essential part of the oxidative phosphorylation system, which arouses cellular homeostasis and energy production. [ 28 ] The expression of MT-ND1 is reduced in Parkinson disease with dementia (PDD).…”
Section: Discussionmentioning
confidence: 99%
“…The Warburg effect confers a growth advantage on cancer cells and HK2 has a vital role in this process (9,19). High expression levels of HK2 have been observed in LC cells (20,21). HK2 was here revealed to accelerate LC cell proliferation and glycolytic metabolism, as evidenced by an increase in mitochondrial respiration, and decreases in glucose uptake capacity, lactic acid content, glycolytic flux and proliferation in HepG2 cells following transfection with si-HK2.…”
Section: Discussionmentioning
confidence: 73%
“…Both the membrane localization and the glucose uptake of GLUT1 play important roles in the Warburg effect. 20 In this study, we have provided evidence that the overexpression of both E6 and E7 in HPV16 down-regulated the expression level of miR-451 in lung cancer cells. However, because the carcinogenesis mechanism of E6 and E7 proteins is not the same, the regulation pathways of miR-451 by both proteins may not be the same.…”
Section: Discussionmentioning
confidence: 69%